Development of Intercultural Communication Learning Materials Based on Needs Analysis - Tanti Kurnia Sari; Surya Masniari Hutagalung; Indah Aini (BIRCU, 2020)
In learning German as Foreign Language (DaF – Deutsch als Fremdsprache), students in The German Language Program at The State University of Medan need to comprehend not only four competencies (Sprechfertigkeit, Lesefertigkeit, Hörfertigkeit, and Schreibfertigkeit), but they also required to have intercultural communication competence. This competence is crucial because there are so many differences between German cultures and Indonesian cultures. This research was conducted at the Faculty of Language and Arts, State University of Medan, in the German Language Education Study Program. The research and development method used in this study refers to Plomp's model, which consists of five steps, namely (1) investigation, (2) design, (3) development realization, (4) evaluation, and (5) implementation. However, in this study, the development process is focused on 3 steps, namely investigation, design, and development realization. Data collection techniques in this needs analysis are questionnaires, literature reviews, and interviews. The data to be analyzed in this study is qualitative data from interviews, observations, and documents. The data were obtained through a questionnaire distributed to 20 alumni of the German Language Study Program who live in Germany. Interkulturelle Kommunikation learning materials were developed based on the results of the questionnaire analysis. The results showed that the learning materials developed included the themes of Familie, Nachbarschaft, Schulsystem in Deutschland, Berufswelt, and Feste, Sinne und Bräuche.